Combined Effects of High-Intensity Aerobic Exercise Training and Ziziphus jujuba Extract on Tissue Nesfatin-1 in Rats - Ghanbari-Niaki, Abbass; Hosseini, Fahimeh; Broom, David Robert; Tejenjari, Bahareh; Rahmati-Ahmadabad, Saleh (Frontiers in Endocrinology, 2022)
Nesfatin-1 is involved in metabolic/feeding regulation and prevention of cardiovascular disease. Previous studies have shown that exercise and herb supplementation can influence nesfatin-1 concentration. The present study investigated the effects of high-intensity training (HIT) and Ziziphus jujuba (ZJ) extract on tissue nesfatin-1 in rats. Twenty-eight female rats were randomly assigned to one of four groups i.e. 1) Saline-Control (SC), 2) Saline-High Intensity Training (ST), 3) Ziziphus jujuba-Control (ZJC), and 4) Ziziphus jujuba-High Intensity Training (ZJT). Rats performed exercise on a treadmill and/or administered supplements intragastrically for 6 weeks, depending on group category. Seventy-two hours after the last training session, rats were anesthetized. Blood, hypothafi 2lamus tissue, heart and gastrocnemius muscles were sent to the laboratory for analyses. Significantly higher nesfatin-1 gene expression and concentration and ATP concentration were found in trained rat. HIT increased plasma High Density Lipoprotein (HDL) and insulin concentration and reduced plasma Triglyceride (TG) and cortisol. ZJ increased tissue nesftain-1 gene expression and concentration while only increasing heart ATP. The combination of exercise and ZJ showed an additive effect compared to each intervention alone on hypothalamus, heart and gastrocnemius NUCB2 gene expression, heart and gastrocnemius nesfatin-1 concentration, plasma HDL and cortisol concentration. The authors recommend both interventions as a means to improve cardiovascular health in rats with further work needed to confirm similar findings in homo sapiens.